Sodium Periodate as a Selective Oxidant for Diclofenac Sodium in Alkaline Medium: A Quantum Chemical Approach - Madhu Gupta; Amrita Srivastava; Sheila Srivastava (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Diclofenac sodium is a well known anti-inflammatory drug. It has also been proclaimed to exhibit adverse effects on aquatic animals through sewage and waste water treatment plants. Kinetic and mechanistic studies of the novel oxidation of diclofenac sodium (DFS) by sodium periodate were discussed with an emphasis on structure and reactivity by using kinetic and computational approach. The proposed work had been studied in alkaline medium at 303 K and at a constant ionic strength of 0.60 mol.dm−3. Formation of [2-(2,6-dicloro-phynylamino)-phenyl]-methanol as the oxidation product of DFS is confirmed with the help of structure elucidation. The active species of catalyst, oxidant and oxidation products were recognized by UV and IR spectral studies. Proton inventory studies in H2O−D2O mixtures had been shown the involvement of a single exchangeable proton of OH− ion in the transition state. All quantum chemical calculations were executed at level of density functional theory (DFT) with B3LYP function using 6-31G (d,p) basis atomic set for the validation of structure, reaction and mechanism. Molecular orbital energies, nonlinear optical properties, bond length, bond angles, reactivity, electrophilic and nucleophilic regions were delineated. Influence of various reactants on rate of chemical reaction were also ascertained and elucidated spectro-photometrically. Activation parameters have been assessed using Arrhenius-Eyring plots. A suitable mechanism consistent with observed kinetic results had been implicated and rate law deduced. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).